Marina Carr's Hecuba: agency, anger and correcting Euripides. Issue 4 (2nd October 2019) - Wallace, Clare
ABSTRACT: This paper focuses on Marina Carr's 2015 adaptation of Hecuba for the Royal Shakespeare Company. Hecuba sees Carr return to a fascination with Greek tragedy, difficult female characters and reimagining foundational myths. Of all Euripides' plays Hecuba has rarely been popular, yet the themes Carr prises open – of violence, desire, gendered experience and the politics of perspective – are acutely topical. Indeed, Hecuba seemed to anticipate the frustrations that erupted on 28 October 2015 in response to the Abbey Theatre's "Waking the Nation" programme. Drawing on twentieth and twenty-first century debates around the politics of tragic form, Roland Barthes theorising of myth, and the tradition of Greek adaptation in modern Irish drama, this paper examines how Hecuba reorients its sources. It goes on to assess the outcomes of these reorientations in order to problematise the critical predisposition to find an inevitably progressive poetics/politics in her engagement with tragic myths.